First report of Haemaphysalis juxtakochi Cooley, 1946 (Acari: Ixodidae) parasitizing horses in Uruguay (FAVE Sección Ciencias Veterinarias, 2019)
The first report of Haemaphysalis juxtakochi Cooley, 1946 parasitizing horses in Uruguay is presented. Adults of this tick species were found in an equine together with Rhipicephalus microplus (Canestrini, 1888), in a locality of the department of Tacuarembó with presence of dense native forest and wildlife abundant, as well as the gray-brocket deer (Mazama gouazoubira) preferential host of H. juxtakochi adults. With this finding there are four species of ticks that can be found parasitizing equines in Uruguay: R. microplus, Amblyomma tigrinum Koch, 1844, Amblyomma triste Koch, 1844 and H. juxtakochi. The medical-veterinary importance of H. juxtakochi in equines is unknown.
Keywords: Haemaphysalis juxtakochi; Ixodidae; horses; Uruguay